Efficient methods to overcome Rabin cryptosystem decryption failure - Mahad, Zahari; Asbullah, Muhammad Asyraf; Kamel Ariffin, Muhammad Rezal (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
Rabin cryptosystem is an efficient factoring-based scheme, however, its decryption produces 4-to-1 output, which leads to decryption failure. In this work, in order to overcome the 4-to-1 decryption problem for the Rabin cryptosystem, we propose two distinct methods using the modulus of the type N=p2q coupled with the restriction on the plaintext space M. In the first method, the plaintext space is limited to M ∈ Zpq. For the second method, we restrict the plaintext in the range of M ∈ (0,22n−2). Importantly, we prove that the decryption output of the proposed methods is unique and without decryption failure. The results in this work indicate that the decryption problem of Rabin cryptosystem is overcome.